Exposing university students to breaking news applications on mobile devices and the gratifications achieved from them - Falah Taher Rahima _ Hussein Ameer Abbas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The research problem's deals , studying the reasons that push the public to use mobile phone applications by looking at the urgent news in them and the gratifications achieved from them. The research is descriptive and using the field survey method, through a survey of students of the College of media at the Iraqi University, and the research reached several conclusions, the most prominent of which are: